Linear one-dimensional color feature for starfruit classification - Mohd. Mokji, Musa (2007)
Malaysia has been the largest exporter of starfruits in the world since 1989 [1]. The biggest starfruit farm has also been setup in Selangor in 2002 [2]. It becomes a serious production because the fruit is not only to be fond among Malaysian but also to the other communities over the world. Over the years, significant export growth has been recorded. Malaysia’s export figures for 2000 and 2001 are 8,745 metric ton and 9,182 metric ton respectively. This is more than 60% increase from Malaysia’s export in 1991, which was 2,723 metric ton [3]. Some of the major starfruit importers include the Netherlands, Germany, Singapore and Hong Kong. These four major importer countries contributed 82.28% to Malaysia’s starfruit export in 2003 [3]. As an export commodity, the production of good quality starfruit is vital because most of the importer countries are a quality conscious customer. These countries are generally less price conscious and they are willing to pay more for good quality exotic tropical fruits such as the starfruit. Thus, an effort towards the best quality production of the starfruit should be discovered. Besides, it will complement Malaysia’s ambition in expanding the agriculture products to support growth in the economy.